PENGINTEGRASIAN MEDIASI DALAM PROSES PERADILAN MERUPAKAN UPAYA MEWUJUDKAN TRILOGI ASAS PERADILAN - Muriani, Muriani; Ningrum, Rinandu Kusumajaya (Jurnal De Lege Ferenda Trisakti, 2024)
Settlement of civil disputes through a negotiation process (mediation) in order to achieve peace between the disputing parties is actually regulated in Article 130 HIR/154 RBg, but the implementation of the provisions in these two articles is not yet optimal so it is necessary to optimize it by integrating mediation into the formal judicial process. With this integration, dispute resolution through a negotiation process to achieve peace is expected to be faster, simpler and less costly, so that the principle of simple, fast and low-cost justice can be realized. The problem is whether this integration can realize the trilogy of justice principles (simple, fast and low cost) and whether peaceful resolution of civil disputes can actually be realized. The research method used in this research is normative juridical, using secondary data supported by primary data obtained through interviews. The author concludes that integrating mediation in the formal justice process can realize the principles of simple, fast and low-cost justice, as long as peace is achieved between the disputing parties, but mediation does not by itself achieve peace